The Effectiveness of a Training Program for Developing Language and Social Communication Skills for Learnable Children with Mental Disabilities - Al-Matt'hami, Dorar Yahya; Al-Matt'hami, Yahya Khader (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the effectiveness of a training program for developing language skills for learnable children with mental disabilities and its relationship to social communication among a sample of learnable children with mental disabilities in Al-Qunfudhah Governorate. The study sample consisted of (n=10) children with mental disabilities aged between 4 to 6 years old.In order to achieve the goals of the study, the researchers used the language skills scale and the social communication scale for people with mental disabilities. After verifying the validity and stability of the tools, the researchers used the quasi-experimental quantitative method for its suitability for the purposes of the study and to answer its questions. The study was conducted over a period of three months, three days per week.The results study showed that there were statistically significant differences between the mean scores of the children of the experimental group in the pre and post measurements of the application of the program on the language skills scale, and the measure of social communication in favor of the post-measurement, and there were no statistically significant differences between the mean scores of the children of the experimental group in the post and follow-up measurements. To apply the program on the language skills scale and the social communication scale.
Keywords: Program; language skills; Social communication; Mental Retardation; Teachable Children with Mental Disabilities